Intracellular Ca2+ signalling: unexpected new roles for the usual suspect - Moccia, Francesco; Fiorio Pla, Alessandra; Lim, Dmitry; Lodola, Francesco; Gerbino, Andrea (Frontiers in Physiology, 2023)
Cytosolic Ca2+ signals are organized in complex spatial and temporal patterns that underlie their unique ability to regulate multiple cellular functions. Changes in intracellular Ca2+ concentration ([Ca2+]i) are finely tuned by the concerted interaction of membrane receptors and ion channels that introduce Ca2+ into the cytosol, Ca2+-dependent sensors and effectors that translate the elevation in [Ca2+]i into a biological output, and Ca2+-clearing mechanisms that return the [Ca2+]i to pre-stimulation levels and prevent cytotoxic Ca2+ overload. The assortment of the Ca2+ handling machinery varies among different cell types to generate intracellular Ca2+ signals that are selectively tailored to subserve specific functions. The advent of novel high-speed, 2D and 3D time-lapse imaging techniques, single-wavelength and genetic Ca2+ indicators, as well as the development of novel genetic engineering tools to manipulate single cells and whole animals, has shed novel light on the regulation of cellular activity by the Ca2+ handling machinery. A symposium organized within the framework of the 72nd Annual Meeting of the Italian Society of Physiology, held in Bari on 14–16th September 2022, has recently addressed many of the unexpected mechanisms whereby intracellular Ca2+ signalling regulates cellular fate in healthy and disease states. Herein, we present a report of this symposium, in which the following emerging topics were discussed: 1) Regulation of water reabsorption in the kidney by lysosomal Ca2+ release through Transient Receptor Potential Mucolipin 1 (TRPML1); 2) Endoplasmic reticulum-to-mitochondria Ca2+ transfer in Alzheimer’s disease-related astroglial dysfunction; 3) The non-canonical role of TRP Melastatin 8 (TRPM8) as a Rap1A inhibitor in the definition of some cancer hallmarks; and 4) Non-genetic optical stimulation of Ca2+ signals in the cardiovascular system.